2019
DOI: 10.1016/j.cemconcomp.2018.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale modeling of ion diffusion in cement paste: electrical double layer effects

Abstract: Understanding the mechanism of ion diffusion in hardened cement paste is of great importance for predicting long-term durability of concrete structures. Gel pores in calcium silicate hydrate (C-S-H) phase forms dominant pathway for transport in cement paste with low w/c ratios where the electrical double layer effects play an important role. Experimental results suggest that the effective diffusivity of chloride ions is similar as that of tritiated water (HTO) and higher than the sodium ions. This difference c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 72 publications
(106 reference statements)
1
17
0
Order By: Relevance
“…This study is helpful to improve the understanding of the diffusion mechanism of monovalent anions in compacted clays. Although our pore‐scale modeling can hardly deal with heterogeneous porous materials (such as clay rocks) directly within limited computational resources, a multiscale numerical framework will be further developed, similar to the model developed for the cement paste by Yang et al (2019) to simulate ion transport in heterogeneous clay rocks. The pore‐scale modeling has shown to be a robust approach to simulate the diffusion of radionuclides in clays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is helpful to improve the understanding of the diffusion mechanism of monovalent anions in compacted clays. Although our pore‐scale modeling can hardly deal with heterogeneous porous materials (such as clay rocks) directly within limited computational resources, a multiscale numerical framework will be further developed, similar to the model developed for the cement paste by Yang et al (2019) to simulate ion transport in heterogeneous clay rocks. The pore‐scale modeling has shown to be a robust approach to simulate the diffusion of radionuclides in clays.…”
Section: Discussionmentioning
confidence: 99%
“…This was usually attributed to the effect of electrical double layer (EDL) when an electrolyte was in contact with the negatively charged surface of clays. The previous studies showed that the EDL had significant impacts on the diffusion of anions in compacted clays (Appelo, 2017; Soler et al, 2019; Yang et al, 2019). The effective diffusion coefficient ( D e ) of anions at a trace concentration increased with increasing ionic strength due to the decrease of EDL thickness (Idiart & Pękala, 2016; Tinnacher et al, 2016; Xiong & Jivkov, 2018).…”
Section: Introductionmentioning
confidence: 97%
“…These indicate that the predicted ionic diffusivity considering the contribution of C-S-H is 4-6 times that only considering the ionic diffusion through capillary pores in cement paste and neglecting the contribution of gel pores in C-S-H. This can be ascribed to the fact that part of capillary pores are isolated or dead-ended which are not effective channels for ionic diffusion [62]. For example, the volume fractions of connected capillary pore in virtual cement pastes with fly ash replacement ratios of 0% and 20% calculated using the burning algorithm [46] are only 0.44 and 0.40, respectively.…”
Section: Contribution Of Capillary Pore and C-s-h Gel To Overall Ionimentioning
confidence: 94%
“…Gel pores in C-S-H are generally of nano-meter size and is smaller than 0 due to the increasing viscosity of pore solution in nanopores [59,60] and the surface effect, i.e. electrical double layer effect [61][62][63]. The average value of is normally regarded as around 10 -10 m 2 /s [60].…”
Section: Determination Of Input Parametersmentioning
confidence: 99%
“…They showed that the chloride diffusion coefficient decreased with the increase of the compressive volumetric strain but increased with an increasing tensile volumetric strain. Yang et al [28] proposed a multiscale modeling technique to analyze the transport of chloride ions in cement paste and demonstrated that the contribution of the Stern layer to ion transport was not negligible for pores with a diameter less than 10 nm. Based on the reconstructed microstructure of hardened cement paste, Carrara et al [29] used a modified Fick’s law to simulate the chloride diffusion coefficient and verified the numerical method with experimental results obtained from the literature.…”
Section: Introductionmentioning
confidence: 99%